Reinvigorating Springfield's economy: Lessons from resurgent cities - Yolanda K. Kodrzycki; Ana Patricia Mu\~noz; Lynn Browne; DeAnna Green; Marques Benton; Prabal Chakrabarti; David Plasse; Richard Walker; Bo Zhao (Federal Reserve Bank of Boston, 2009)
As part of the Federal Reserve Bank of Boston's commitment to supporting efforts to revitalize the economy of Springfield, Massachusetts, this paper analyzes the economic development approaches of other mid-sized manufacturing-oriented cities during the past half century. From among a comparison group of 25 municipalities that were similar to Springfield in 1960, the study identifies 10 'resurgent cities' that have made substantial progress in improving living standards for their residents, and that are recognized as vital communities in a broader sense by experts on urban economic development and policy. These case studies suggest that industry mix, demographic composition, and geographic position are not the key factors distinguishing the resurgent cities from Springfield. Instead, the most important lessons from the resurgent cities concern leadership and collaboration. Initial leadership in these cities came from a variety of key institutions and individuals. In some cases, the turnaround started with efforts on the part of the public sector, while in other cases nongovernmental institutions or private developers were at the forefront. Regardless of who initiated the turnaround, economic redevelopment efforts spanned decades and involved collaborations among numerous organizations and sectors.
Keywords: R0; N0; 330